ANALISIS DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI KEUANGAN PADA SMKS PGRI 1 KOTA JAMBI - Lestari, Ayu; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2019)
Management process of the financial administration at SMKS PGRI I Jambi City is still done manuallydate book that is using at the payment of spp , money computer practices , money the test and op3 ( osis ,pmr , the library , scout ) so that in the management of financial administration is still take a long timeand slow , inefficient , as well as the results were not accurate .The solution offered information systemsthat the change is based a database .As for the purpose of this research is to analyze and design systemsinformation financial administration the successful students at smks pgri one city jambi with benefitgained that is making it easier in the management of financial administration and reporting to the schoolprincipal , and able to minimize the time, so in the management of financial administration can be done atthe correct time , fast and accurate. The tools modeling a system used that is using dfd ( data flowdiagram ) with an output that produced in the form of the prototype of to the reports on the reception ofpay , to send daily report , the report and the report on student data as of the payment of .And in buildingprototypes has still not been concerned about data security system so it is suggested for subsequentdevelopment is expected to be furnished with data security